Endometrial assessment by transvaginal ultrasonography and correlation with histopathology among post menopausal women (Journal of Pathology of Nepal, 2020)
Background: Transvaginal ultrasonography has increased the reliability of imaging diagnosis of women with endometrial pathologies and this technique has become widely used to evaluate endometrial thickness in women with postmenopausal bleeding.Materials and methods: 359 women presenting with history of at least three months amenorrhea were undergone transvaginal ultrasonography with measurement of endometrial thickness and uterine size. Endometrial biopsies were taken in 69 cases (19.2%) only.Results: The median age of patients was 53 years with the age range of 42 years to 81 years. Abdominal pain was the commonest symptoms followed by backache. 3/69 cases with histopathological diagnoses had normal sized uterus, while 66 cases had bulky (>6.0 cm) uterus. 58/69 cases showed > 5 mm thick endometrium and the endometrium was abnormal in 31/69 cases. The sensitivity, specificity, positive predictive value and negative predictive value of transvaginal ultrasonography to detect abnormal endometrium were 91.2%, 22.9%, 53.4% and 72.7% respectively. The sensitivity, specificity, positive predictive value and negative predictive value of transvaginal ultrasonography to detect endometrial hyperplasia and carcinoma were 100%, 17.5%, 10.3% and 100% respectively.Conclusions: Transvaginal sonographic evaluation of endometrial thickness and uterine size is useful for exclusion of endometrial pathology and to avoid unnecessary invasive surgical procedures.